Constructing discourse: an experimental approach - Recio Fernández, Inés; Loureda Lamas, Óscar; Sanders, Ted (Revista Signos, 2021)
Abstract: This contribution aims at offering a state of the art about experimental research on mechanisms for referential and relational coherence, pivotal for the construction of discourse in the interlocutors’ aim to recover of a relevant assumption in communication. The construction of discourse is a cognitive ‘activity’ that consists in decoding linguistic material of utterances and performing a series of mental operations to recover a relevant interpretation in a communicative exchange. For that purpose, interlocutors put to use linguistic mechanisms directed at establishing ‘referential coherence’ and ‘relational coherence’ to achieve discourse ‘connectedness’. The cognitive effects of these mechanisms in terms of their consequences for discourse processing and interpretation can be approached by means of experimentation. Doing so allows the researcher to enrich scientific findings as provided by linguistic description and observational studies, helps refining theories of human verbal communication and comes along with a strong transfer potential for applied endeavors.Key Words: Referential coherence; relational coherence; discourse marking; cognitive effort; experimentation
Gesehen am 17.02.2022